Giant coronary aneurysm culprit of an acute coronary syndrome - Iván J. Núñez-Gil; Pedro Marcos Alberca; Nieves Gonzalo; Luis Nombela-Franco; Pablo Salinas; Antonio Fernández-Ortiz (Revista Portuguesa de Cardiologia, 2018)
A 66-year-old male ex-smoker with hypertension, type 2 diabetes mellitus and dyslipidaemia was admitted due to a non-ST segment elevation myocardial infarction. The catheterisation depicted an extensive and calcified disease: chronic total obstruction of the right coronary and severe disease with a giant aneurysm at the first marginal branch as the culprit vessel. After discussion, the right coronary was treated before the circumflex-giant aneurysm was closed with a stent graft and its multiple severe stenosis solved with two drug-eluting stents. We provide a multimodality approach for a complex case and briefly discuss the available options. Resumo: Um homem de 66 anos, ex-fumador, hipertenso, com diabetes tipo II e dislipidemia, foi admitido por enfarte do miocárdio sem supradesnivelamento de ST. O cateterismo revelou doença extensa e calcificada: oclusão crónica e total da artéria coronária direita e doença severa com aneurisma gigante da primeira obtusa marginal, como lesão alvo. Após discussão, foi tratada a artéria coronária direita e posteriormente foi encerrado o aneurisma gigante de circunflexa com um stent e as suas múltiplas estenoses severas foram resolvidas com dois stents com fármaco. Providenciamos uma abordagem multimodal para um caso complexo e discutimos brevemente as diferentes opções possíveis. Keywords: Acute coronary syndrome, Coronary aneurysm, OCT, IVUS, CT-scan, Multimodality, Palavras-chave: Síndrome coronária aguda, Aneurisma coronário, OCT, IVUS, CT-Scan, Multimodalidade